"Collaborative-ready" students: Exploring factors that influence collaboration during a longitudinal interprofessional education practice experience. Issue 2 (3rd March 2016) - Rotz, Melissa E.; Dueñas, Gladys G.
ABSTRACT: A goal of interprofessional education (IPE) is to prepare "collaborative-ready" healthcare professionals to ultimately improve health outcomes. The objective of our study was to explore student-reported factors that influence collaboration within our longitudinal IPE experience. Twenty-five first-year pharmacy students and 50 first-year medical students enrolled in IPE courses were invited to participate in three focus groups. Focus group responses were audio-recorded, transcribed verbatim, and applied to a qualitative thematic analysis. Eighteen students participated with six students in each group. Compared to the medical students, the pharmacy students were younger (22 vs. 26 years), had earned only a high school diploma, and had less healthcare experience. Emergent themes that students reported revealed various factors that can facilitate and inhibit collaboration among student participants. These findings can inform curricular redesign to focus on: clarifying provider roles, requiring ongoing preceptor development, enhancing course orientation, and coordinating student schedules to better prepare "collaborative-ready" students.